Two Treatises of Philo of Alexandria A Commentary on De Gigantibus and Quod Deus sit Immutabilis - Winston, David (Brown Judaic Studies, 2020)
This is a detailed commentary on two paradigmatic books of the Jewish philosopher, Philo of Alexandria.